2022
DOI: 10.3390/su14127106
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprints and Life Cycle Assessments of Inhalers: A Review of Published Evidence

Abstract: Respiratory inhalers have a substantial impact on the carbon footprint of the healthcare sector. Environmental factors, including carbon footprints, are gaining importance in choosing inhalers once medical considerations have been addressed. This paper provides a review of the carbon footprint (CFP) and life cycle assessment (LCA) environmental profile of dry powder inhalers (DPIs) and pressurized metered-dose inhalers (pMDIs). Despite methodological challenges, our analysis reveals that the CFP varies between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…dry-powder instead of metred-dose inhalers 60 ), the uptake of most of these initiatives is reliant on changes in healthcare practice. This review identified a range of interventions that have been implemented with most relying on behavioural change of individual clinicians.…”
Section: Original Researchmentioning
confidence: 99%
“…dry-powder instead of metred-dose inhalers 60 ), the uptake of most of these initiatives is reliant on changes in healthcare practice. This review identified a range of interventions that have been implemented with most relying on behavioural change of individual clinicians.…”
Section: Original Researchmentioning
confidence: 99%
“…Factors such as plastic and metal pollution also contribute to environmental damage; but carbon footprint is the best described environmental impact of inhalers 19…”
Section: What Is the Problem?mentioning
confidence: 99%
“…Encourage practitioner behaviour change to favour DPIs (and SMIs) over pMDIs 1927. A post hoc analysis of 2236 patients in England showed reduced asthma symptoms and greater productivity in daily activities in patients switching from pMDI to DPI 27…”
Section: What Are the Solutions?mentioning
confidence: 99%